Relationship between characteristics of pregnant women and knowledge of pregnant women regarding obstetric emergencies - Aufa, Naimatul; Santoso, Izal Puji; M. Tajaruddin; Yulyanti, Yulyanti; Yunita, Yunita (Sean Institute, 2023)
Pregnant women's knowledge of the danger signs of pregnancy is an early prevention of risks that can occur in pregnancy. The aim of this research was to determine the relationship between the characteristics of pregnant women and the knowledge of pregnant women regarding obstetric emergencies at Banjarmasin Hospital. The sample consisted of 42 respondents. The research design used was a cross sectional design and data was collected from respondents using a questionnaire sheet. The research results show that in this study there is a relationship between education level and mother's knowledge with a value of ρ = 0.007, there is a relationship between age and mother's knowledge with a value of ρ = 0.000, there is no relationship between experience and mother's knowledge with a value of ρ = 1.000 and there is a relationship between exposure to information. with mother's knowledge the value ρ = 0.000. The conclusion shows that there is a significant relationship between the characteristics of pregnant women and pregnant women's knowledge about obstetric emergencies. It is recommended that pregnant women be able to recognize the danger signs in pregnancy and be able to carry out early detection of danger signs in pregnancy.